Clinical And Haematological Study Of Lactating Cattle, Reared Around A Thermal Power Plant, Showing Horn And Hoof Abnormalities (Applied Biological Research, 2015)
The present study was aimed to assess clinic-haematological changes in  cows showing hoof and horn abnormalities, rearedaround Koradi Thermal  Power Plant, Nagpur, Maharashtra (India). Hoof and horn abnormalities  are usually attributed to selenium toxicity. Twenty cows were randomly  selected within a radius of 5 km of thermal power plant. Blood, urine and  milk samples were analyzed for haemato-biochemical changes. Also, the  selenium level was estimated and compared with control samples taken  from Deolapar Cattle Farm and Agriculture CollegeDairy Farm (located  within the same agro-climatic conditions but away from the impact area of  fly ash). Mean selenium value in blood of exposed animals was  insignificantly higher than unexposed animals while selenium in urine and  milk of exposed cows was significantly higher than control though within  the permissible range. The haemato-biochemical parameters viz.,  haemoglobin, AST, ALT, serum creatinine and BUN of exposed cows were  insignificantly less than control cows. Air, water, soil and fodder samples,  collected from the study area, showed the selenium level of 3 ng m-3,  0.001±0.002 ppm, -0.593 ppm and 1.25±0.20 ppm, respectively. It appears  that the selenium level in impact area has not reached to the level that may  develop selenium toxicity like sloughing of horns, weakness and hoof  deformity; and the symptoms observed are due to the factor other than  selenium toxicity.
Keywords: Cow; flyash; haemato-biochemical parameters; lactation; selenium; thermal power plant